2023
DOI: 10.3390/molecules28031434
|View full text |Cite
|
Sign up to set email alerts
|

Homoleptic Complexes of Heterocyclic Curcuminoids with Mg(II) and Cu(II): First Conformationally Heteroleptic Case, Crystal Structures, and Biological Properties

Abstract: We report herein the synthesis and characterization of three heterocyclic curcuminoid ligands and their homoleptic metal complexes with magnesium and copper. Thus, N-methyl-2-pyrrolecarboxaldehyde, Furan-2-carboxaldehyde, and 2-Thiophenecarboxaldehyde were condensed with 2,4-pentanedione-boron trioxide complex. The first N-methyl-2-pyrrole curcuminoid and its Mg(II) complex are reported. All curcuminoid ligands and their corresponding metal complexes were characterized by infrared spectroscopy (IR), liquid sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Antioxidant activity of curcumin and curcumin–copper complex were tested by Thiobarbituric Acid Reactive Substances (TBARS) method and were measured using rat brain homogenates according to the method described by Ng and co-workers [ 75 ], with some modifications as previously was recorded [ 76 ]. The concentration of TBARS was calculated by interpolation on a standard curve of tetra-methoxypropane (TMP) as a precursor of MDA [ 77 ].…”
Section: Methodsmentioning
confidence: 99%
“…Antioxidant activity of curcumin and curcumin–copper complex were tested by Thiobarbituric Acid Reactive Substances (TBARS) method and were measured using rat brain homogenates according to the method described by Ng and co-workers [ 75 ], with some modifications as previously was recorded [ 76 ]. The concentration of TBARS was calculated by interpolation on a standard curve of tetra-methoxypropane (TMP) as a precursor of MDA [ 77 ].…”
Section: Methodsmentioning
confidence: 99%
“…The curcuminoid complexes of Zn we recently reported provide an example of different geometries, including octahedral, trigonal pyramidal, and trigonal bipyramidal [15]. The heterocyclic curcuminoid complexes with Mg and Cu provide an example of the first conformationally heteroleptic complexes [16]. To the best of our knowledge, no theoretical approach has predicted any of the experimental cases mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, In 3+ has ionic radii ranging from 62 pm to 92 pm, leading to tetracoordinate, hexacoordinate, and octacoordinated complexes [13]. In our previous work [14][15][16], we have found that the X-ray structure determinations are critical for establishing the stoichiometric relationships to the metal, geometry, and the conformations of ligands. The curcumin-copper complex recently reported provides a suitable ML 2 example [14].…”
Section: Introductionmentioning
confidence: 99%
“…The β-diketone scaffold is not very common in nature, though it is the main feature of curcumin and its derivatives [11][12][13] and, in recent years, many metal complexes of curcumin and curcuminoids have been reported and evaluated as anticancer agents [14][15][16][17][18][19][20][21][22][23][24][25][26]. In fact, β-diketones are known to form complexes with almost every metal, and they have been used as supporting ligands for Ti(IV)- [27,28], Ru(II)- [29][30][31][32][33][34][35], Pd(II)- [36] and Ptbased anticancer agents [37][38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%